Note on the Hardness of Bounded Budget Betweenness Centrality Game with Path Length Constraints - Bei, Xiaohui; Chen, Wei; Zhang, Jialin (2009)
In this technical report, we generalize the betweenness definition in Bounded Budget Betweenness Centrality Game (called B3C game) introduced in [MSR-TR-2008-167] to only count shortest paths with a length limit l. We denote this game l-B3C game. We prove that the hardness results in [MSR-TR-2008-167] about nonuniform game still hold in this generalized version.